GABABR activation partially normalizes acute NMDAR hypofunction oscillatory abnormalities but fails to rescue sensory processing deficits. Issue 5 (25th March 2022) - Janz, Philipp; Nicolas, Maria Jesus; Redondo, Roger L.; Valencia, Miguel
Abstract: Cognitive deficits and impaired sensory processing are hallmarks of several neurodevelopmental and neuropsychiatric disorders. N ‐methyl‐d ‐aspartate receptor (NMDAR) hypofunction contributes to these deficits by disrupting the excitation‐to‐inhibition balance in neuronal networks. Although preclinical data suggest that the activation of gamma‐Aminobutyric acid B receptors (GABAB R) may restore excitation‐to‐inhibition balance and rescues some behavioral deficits, GABAB R agonists have failed to meet their clinical study endpoints, suggesting more complex interactions at play. Here, we studied the effects of Baclofen (a GABAB R agonist) and MK‐801 (a non‐competitive NMDAR antagonist) on the neurophysiology of limbic‐auditory circuits in freely‐moving rats. The pharmacological effects were assessed using resting‐state EEG, auditory‐evoked oscillation, and mismatch negativity paradigms. MK‐801 elevated resting‐state oscillatory power, mainly in the gamma and higher frequency ranges, and impaired auditory‐evoked responses. Baclofen partially normalized resting‐state oscillations but failed to rescue auditory‐evoked oscillatory abnormalities. Coherence analysis indicated that NMDAR hypofunction alters the functional coupling of limbic and thalamocortical circuits in several frequency bands. Baclofen normalized only a fraction of MK‐801‐induced abnormalities (e.g., theta coherence between frontal cortex and amygdala) while reducing delta‐theta and augmenting gamma coherence in thalamocortical circuits. Finally, we report that Baclofen intensified the MK‐801‐induced deficits in auditory mismatch responses. In summary, while Baclofen partially normalizes MK‐801‐induced gamma abnormalities, it either fails to rescue or exacerbates deficits in other phenotypes like functional coupling and auditory processing. We hope that the presented complex interactions between pharmacologically induced NMDAR hypofunction and GABABR agonism inspire a new understanding of the therapeutic potential around GABAergic modulation. Abstract : Taking advantage of multi‐site electrophysiological recordings and a selection of highly translational readouts in freely moving rats, this study provides a comprehensive description of the effects of GABABR activation, using baclofen, in a pharmacological model for NMDAR hypofunction, using MK‐801. We show that baclofen application partially normalizes gamma oscillations and coherence abnormalities induced by MK‐801, but at the same time fails to restore sensory abnormalities and even elicits potential detrimental effects. Therefore, our study informs about possible therapeutic opportunities and limitations of GABABR modulation in disorders associated with NMDAR hypofunction. (Created with BioRender.com).